Hemorrhagic Transformation in Pneumococcal Meningitis: A Rare but Devastating Complication (Bangladesh Critical Care Journal, 2025)
Bacterial meningitis is a neurological emergency with significant morbidity and mortality. Streptococcus pneumoniae is the leading cause in adults, with complications such as cerebral infarction, hydrocephalus, and seizures. Haemorrhagic transformation is extremely rare, reported in 2–9% of cases, but is associated with poor prognosis. We report a case of pneumococcal meningitis complicated by extensive frontal lobe and cerebellar haemorrhages. The patient presented with classic meningitis symptoms and rapidly developed a generalized tonic–clonic seizure. Neuroimaging revealed multiple haemorrhages without vascular malformations, hypertension, anticoagulant exposure, or coagulopathy. Venous sinus thrombosis was excluded. Systemic sepsis and vasculitis were considered the likely contributors to haemorrhagic transformation. Despite the severity, the patient showed significant neurological recovery following targeted antibiotics, intensive care, and multidisciplinary rehabilitation. This case emphasizes the need for early neuroimaging in meningitis patients with neurological decline, even in the absence of vascular risk factors, to enable timely recognition and intervention.Bangladesh Crit Care J September 2025; 13 (2): 120-123